Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India - Islam, Md Niraul; Ahmad, Wasim (European Journal of Taxonomy, 2021)
Five new and five known species of the genus Tylencholaimus de Man, 1876 are described from the Western Ghats of India. Tylencholaimus macroamphidius sp. nov. has a 0.61–0.85 mm long body, angular lips, large amphid, 8.0–9.0 μm long odontostyle, odontophore with asymmetrical basal knobs, pharyngeal bulb expanding gradually, female genital system mono-prodelphic, and a rounded to conoid tail. Tylencholaimus shamimi sp. nov. has a 0.57–0.71 mm long body, 6.0–7.0 μm long odontostyle, odontophore with basal thickening, pharyngeal bulb expanding gradually, female genital system amphidelphic and a convex-conoid tail. Tylencholaimus southindicus sp. nov. has a 0.44–0.55 mm long body, lip region with distinct labial disc, 4.5–5.5 μm long odontostyle, odontophore with minute basal knobs, pharyngeal expansion abrupt, female genital system mono-prodelphic, and a rounded-conoid to rounded tail. Tylencholaimus striatus sp. nov. has a 0.30–0.34 mm long body with distinctly striated cuticle, 5.0–5.5 μm long odontostyle, odontophore with minute basal knobs, pharyngeal bulb expanding abruptly, female genital system mono-prodelphic, and a conoid tail with bluntly rounded terminus. Tylencholaimus tamiliensis sp. nov. has 0.51–0.58 mm long body, 5.5–6.0 μm long odontostyle, odontophore with minute basal knobs, pharyngeal bulb expanding gradually, female genital system mono-prodelphic and tail rounded to conoid with sunken terminus. Five known species of the genus Tylencholaimus viz. T. mirabilis, T. teres, T. micronanus, T. ibericus and T. cosmos also recorded from the region and redescribed/illustrated.